2009
DOI: 10.1590/s0034-71672009000100011
|View full text |Cite
|
Sign up to set email alerts
|

Risco para trauma vascular: proposta do diagnóstico e validação por peritos

Abstract: RESUMO RESUMO RESUMO RESUMO RESUMO Pesquisa de validação conceitual e de conteúdo que objetivou compor o título, os mecanismos de vulnerabilidade e os fatores de risco para o diagnóstico de enfermagem "Risco para Trauma Vascular", segundo a taxonomia da NANDA, bem como validar os elementos desse diagnóstico, a partir da opinião de 60 peritos. Foram identificados 51 fatores relacionados a cinco eixos: medicação e forma/ periodicidade de infusão; cateter intravascular e permanência num mesmo sítio; fixação do ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 26 publications
2
29
0
13
Order By: Relevance
“…Other studies of content validation showed higher, similar or lower number of experts when compared to the number of experts in this search: 120 nurses (nursing diagnosis of anxiety) (11) , 72 experts (nursing diagnosis of spiritual anguish) (12) (13) , 58 experts (nursing diagnosis of nausea) (14) , 50 experts (diagnosis of deficient knowledge) (4) , 32 experts (diagnostic of sexual dysfunction and ineffective sexuality pattern) (15) , 16 experts (diagnostic of fear and anxiety) (16) , 21 experts (nursing interventions for patients with diabetes mellitus) (17) .…”
Section: Discussionmentioning
confidence: 78%
“…Other studies of content validation showed higher, similar or lower number of experts when compared to the number of experts in this search: 120 nurses (nursing diagnosis of anxiety) (11) , 72 experts (nursing diagnosis of spiritual anguish) (12) (13) , 58 experts (nursing diagnosis of nausea) (14) , 50 experts (diagnosis of deficient knowledge) (4) , 32 experts (diagnostic of sexual dysfunction and ineffective sexuality pattern) (15) , 16 experts (diagnostic of fear and anxiety) (16) , 21 experts (nursing interventions for patients with diabetes mellitus) (17) .…”
Section: Discussionmentioning
confidence: 78%
“…A number of factors have been described as enhancers of possible problems in cancer treatment, which include infiltration, phlebitis or tissue necrosis: the length of cancer treatments; patients' cognitive, sensory and perceptive conditions (1) ; as well as vascular and cutaneous fragility; thrombocytopenia; progressive deterioration of the peripheral venous network (2) ; patients' age (3) ; venous types and conditions (4,5) ; and the therapeutic protocol defining the drugs and their action, dosage, characteristic, volume, concentration and association and established infusion time (3,(6)(7)(8) ; besides the selection of recent puncture sites in the system used for infusion; choice of intravenous devices, use of infusion pump (3,9,10) , fixation form (10,11) , excess circuits linked to the site (11) and tourniquet use to improve the visualization of the vein (11,12) . The North American Nursing Diagnostics Association (NANDA-I) (13) appoints some of these possible risk factors as characteristics of the diagnosis Risk for Vascular Trauma, recently incorporated into Taxonomy II.…”
Section: Introductionmentioning
confidence: 99%
“…Na prática de enfermagem observam-se situações em que estão presentes fatores de risco ou etiológicos de danos à rede venosa ou das estruturas próximas a ela, isto é, lesando diretamente a estrutura do vaso ou de tecidos vizinhos, decorrente quer da presença do dispositivo de infusão ou de líqui-dos infundidos ou drenados Tais alterações são denominadas de risco de trauma vascular ou trauma vascular, respectivamente (Arreguy-Sena & Carvalho, 2007;ArreguySena, 2002). Dentre as causas, destacam-se o contato de líquidos (vesicantes ou não vesicantes) com o espaço extra-vascular ou epiderme, o uso do mesmo sítio para múlti-plas punções ou em pequenos intervalos de tempo, garroteamento por tempo excessivo, correlação indevida entre calibre do vaso e do dispositivo empregado, excesso de circuito sem fixação efetiva, transfixação de vasos ou deslocamento da agulha no interior do vaso, tempo prolongado de uso do mesmo sitio, excesso de adesivos nas áreas adjacentes aos dispositivos, falta de oclusão eficaz, umidade ou sujidade nesses locais (Maki & Ringer, 1991;hadaway, 2002;Phillips, 2005;Bonassa& Santana, 2005;Arreguy-Sena & Carvalho, 2007).…”
Section: Introductionunclassified
“…Dentre as causas, destacam-se o contato de líquidos (vesicantes ou não vesicantes) com o espaço extra-vascular ou epiderme, o uso do mesmo sítio para múlti-plas punções ou em pequenos intervalos de tempo, garroteamento por tempo excessivo, correlação indevida entre calibre do vaso e do dispositivo empregado, excesso de circuito sem fixação efetiva, transfixação de vasos ou deslocamento da agulha no interior do vaso, tempo prolongado de uso do mesmo sitio, excesso de adesivos nas áreas adjacentes aos dispositivos, falta de oclusão eficaz, umidade ou sujidade nesses locais (Maki & Ringer, 1991;hadaway, 2002;Phillips, 2005;Bonassa& Santana, 2005;Arreguy-Sena & Carvalho, 2007). Freqüentes trombocitopenias e fragilidade vascular devido ao déficit nutricional em decorrência da doença também foram apontadas por Bonassa y Santana (2005) como responsáveis pela ocorrência de tais danos.…”
Section: Introductionunclassified